Digital-Based Chemistry Learning Innovation according to IMO Model Course 7.04 in Maritime Education - Nafillah, Khoirotun (Proceeding International Conference on Religion, Science and Education, 2025)
IMO Model Course 7.04 establishes training guidelines for officers in charge of an engineering watch, one of which is through chemistry courses. Innovation in chemistry learning at maritime universities is significant in meeting the competency needs of prospective seafaring students. Unfortunately, many students experience difficulty learning chemistry because chemistry concepts are abstract, and the allocation of learning time is negligible. Students also have difficulty finding chemical reference sources that comply with IMO Model Course 7.04 standards. The research analyzes the existing curriculum and develops innovative digital-based learning strategies by IMO Model Course 7.04 standards. Technology integration in learning includes using websites (e-modules), virtual laboratories, artificial intelligence, and edutainment applications/platforms. The evaluation results show that this innovation improves understanding of chemical concepts and the practical skills students need in the field. With real context through digital-based learning, students can understand the relevance of chemistry in various aspects of the maritime industry. It is hoped that these findings will become a reference for curriculum development in maritime universities and strengthen the contribution of higher education to the needs of the growing industry.